The significance of estrogen receptors in acromegaly: Are they useful as predictors of prognosis and therapy regimen?. (December 2020) - Ozturk, Selma; Donmez-Altuntas, Hamiyet; Ozturk, Figen; Kurtsoy, Ali; Gokay, Ferhat; Simsek, Yasin; Bayram, Fahri
Abstract: Objective: In this study, we considered to assess the presence of estrogen receptors (ER) and the expression of estrogen receptor genes (ESR) in the surgical tissue samples of acromegaly patients and the control group patients with nonfunctioning adenoma and their association with disease activity. We also aimed to determine the significance of ER positivity in acromegaly patients and to find out whether it carries a potential to be used as a predictor of prognosis and therapy regimen in the future. Design: This study was conducted on a total of 67 patients over 18 years of age. The study group consisted of 34 patients with acromegaly and 33 patients with nonfunctioning pituitary adenoma. The pre- and post-operative basal pituitary hormone levels and magnetic resonance images (MRI) of all patients, as well as their remission status of all acromegaly patients were evaluated. Immunohistochemical (IHC) staining procedures for ER-α were performed on surgical tissue samples. Real-time quantitative polymerase chain reaction (RT-qPCR) method was used to determine the levels of ESR1 and ESR2 gene expressions. Results: We found that IHC staining for ER-α was positive in 31.3% and 45.5% of the patients with acromegaly and nonfunctioning adenoma respectively. There was no statistically significant difference of ER-α positivity, ER-α immunoreactivity score and ESR1/ESR2 gene expression levels among the study groups ( p  > .05). Nevertheless, the expression of ESR1 gene was found to be 0.26 times more, and the ESR2 gene to be 0.11 times less in the acromegaly group compared to those of the nonfunctioning adenoma group. Additionally, we detected the positivity of ER-α only in acromegaly patients who were in remission. An inverse association was found between the pre-operative insulin-like growth factor-1 (IGF-1) levels and the expressions of ESR1/ESR2 gene in acromegaly patients. So these results indicated that the high ESR1 and ESR2 gene expressions in acromegaly patients are associated to the decrease of pre-operative IGF-1 values. Also an inverse association was found between the pre-operative adenoma volume and ESR1 Ct values, means that increase in ESR1 gene expression is associated to the decrease of adenoma volume. Conclusions: The current results may suggest the use of these parameters as useful prognostic markers because all ER-positive acromegaly patients were in remission and the high ESR1 and ESR2 gene expressions in acromegaly patients is associated to the decrease of pre-operative IGF-1 values. Our results need to be supported by further studies. Highlights: In the past years estrogen and selective estrogen receptor modulators (SERMs) have been tried in acromegaly patients. The expression of ESR1 gene was 0.26 times more in the acromegaly group compared to the nonfunctioning adenoma group. All ER-α-positive acromegaly patients were in remission. High ESR1/ESR2 gene expressions in acromegaly patients are associated with the decrease of pre-operative IGF-1 values. ER positivity in acromegaly patients may be use as useful prognostic markers.